Business Environment and Start-Up in Indonesia:Empirical Evidence from Province-level Data - Igamo, Alghifari Mahdi; Putra, Agung Raneo; Khamisah, Nur; Kurniawan, Arika (Journal of Economic Development, Environment and People, 2020)
The purpose of this study is to analyze the Effect of the Business Environment on Start-up in Indonesia. This study specifically examines the effect of Gross Regional Domestic Product, Per Capita Expenditure, Unemployment Rate, Total Population, Computer Users and Individual Internet Users which are used as business environment indicators on the existence of startup businesses in 17 Indonesian Provinces during the 2013-2018 period using panel data regression analysis tools to prove that GRDP, Total Population, Computer Users and Internet Users have a positive and significant effect on the existence of start-up businesses in Indonesia. Meanwhile, expenditure per capita and the unemployment rate have a negative effect on the existence of start-up businesses in Indonesia